Design and Implementation of Geological Hazard Data Acquisition System Based on Online Technology. Issue 6 (October 2021) - Zhang, Yanling; Yang, Xudong; Li, Yuan; Tong, Bin; Yin, Chunrong
Abstract: Based on the working process and technical requirements of geological hazard survey in China, a geological hazard field survey data acquisition system was developed based on online technology. The system, capable of presenting remote sensing images or topographic maps with a scale of 1:50, 000 or higher accuracy and providing accurate positioning based on GPS and Beidou system, can satisfy the requirements of geological hazard field data collection. The system provides numerous functions, including data download, survey route navigation, online form filling, graph drawing, photo recording, and data synchronism. The development of the proposed system will provide rapid, accurate, and convenient data collection and information search for geological hazard field survey. The proposed system has been widely applied in practice and has significantly improved the working accuracy and efficiency of geological hazard field survey.